TERT PfeRNA regulates telomere length during cellular senescence of normal human bronchial epithelial cells - Suguru Yamauchi; Kaitlyn Ecoff; Andrei Gurau; Kristen P. Rodgers; Malcolm V. Brock; Yuping Mei (Scientific Reports)
Abstract Telomeres progressively shorten with each cell division in human somatic cells, but the mechanisms governing telomere length remain incompletely understood. Although telomerase reverse transcriptase (TERT) is central to telomere maintenance, the discrepancy between TERT level and telomere length highlights the unidentified molecules that regulate TERT’s functional activities. Here, we identify novel TERT-associated protein functional effector sncRNAs (TpfeRNAs) that modulate telomerase activity and telomere length during cellular senescence of normal human bronchial epithelial (NHBE) cells. We found that in senescent NHBE cells, telomerase activity, TERT mRNA levels, and telomere length were 60%, 2.7%, and 76% of those in proliferative cells, respectively. Using immunoprecipitation and TA cloning assays, we identified TpfeRNAa and TpfeRNAb, which were differentially expressed in proliferative and senescent NHBE cells. Blocking TpfeRNAb in senescent cells increased telomere length by 18% and boosted telomerase activity by tenfold, while ectopic expression of TpfeRNAb in proliferative decreased telomere length by 10%. These findings uncover TpfeRNAb as a key regulator of TERT activity to control telomere length, providing new insights into cellular senescence and aging-related diseases.